2017
DOI: 10.1186/s13071-017-2136-2
|View full text |Cite
|
Sign up to set email alerts
|

Mining a differential sialotranscriptome of Rhipicephalus microplus guides antigen discovery to formulate a vaccine that reduces tick infestations

Abstract: BackgroundTicks cause massive damage to livestock and vaccines are one sustainable substitute for the acaricides currently heavily used to control infestations. To guide antigen discovery for a vaccine that targets the gamut of parasitic strategies mediated by tick saliva and enables immunological memory, we exploited a transcriptome constructed from salivary glands from all stages of Rhipicephalus microplus ticks feeding on genetically tick-resistant and susceptible bovines.ResultsDifferent levels of host ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 75 publications
0
52
0
1
Order By: Relevance
“…(B.) microplus (Maruyama et al, 2017) and the sialotranscriptomes of other tick species (Karim et al, 2011;Díaz-Martín et al, 2013;Radulović et al, 2014;Tan et al, 2015;Ong et al, 2016;Antunes et al, 2018), and they may function in tick feeding by coating the chitinous feeding mouthparts or the feeding lesion (Francischetti, 2010). In 1998, an antigen purified from R.…”
Section: Degs Between Ticks Fed On Tick-susceptible and Resistant Cattlementioning
confidence: 99%
See 2 more Smart Citations
“…(B.) microplus (Maruyama et al, 2017) and the sialotranscriptomes of other tick species (Karim et al, 2011;Díaz-Martín et al, 2013;Radulović et al, 2014;Tan et al, 2015;Ong et al, 2016;Antunes et al, 2018), and they may function in tick feeding by coating the chitinous feeding mouthparts or the feeding lesion (Francischetti, 2010). In 1998, an antigen purified from R.…”
Section: Degs Between Ticks Fed On Tick-susceptible and Resistant Cattlementioning
confidence: 99%
“…This family comprises chymotrypsin, elastase and trypsin inhibitors (Sasaki et al, 2008), although many extracellular proteins also contain multiple TIL domains (Wang et al, 2015). TIL domain-containing protein family members have been found ubiquitously in blood-feeding insect and tick sialomes (Karim and Adamson, 2012;Maruyama et al, 2017), and in fungalpathogen interactions, members of this family are frequently associated with host adaptation or specialization (Schulze-Lefert and Panstruga, 2011).…”
Section: Degs Predicted As Salivary Gland Secreted Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Bmi-MP4 metalloprotease vaccination study in Brazil yielded 60% efficacy as reported in 2015 [29], with no patent published ( Table 2). A different Brazil-based study identified an unrelated metalloprotease Rm239/Sequence 82 (31% identity with Bmi-MP4, data not shown) as a component of a cocktail vaccine of four proteins achieving 73% protection in a tick challenge trial [30]. These proteins were identified through a salivary gland transcriptome study; thus in this instance the researchers were targeting secreted salivary proteins.…”
Section: Secreted Antigensmentioning
confidence: 99%
“…Neste trabalho, nós utilizamos dados de sialotranscriptomas de carrapatos R. Para definir quais proteínas seriam utilizadas a partir de cada grupo funcional, foram considerados os seguintes fatores: (1) nível de expressão gênica, visto que proteínas mais expressas devem estar mais ativas no processo de alimentação; (2) expressão gênica para as diferentes fases do carrapato (adultos, larvas ou ninfas), a fim de selecionar ao menos um antígeno de cada fase; (3) presença de resultados preliminares de proteção e indução de resposta imunológica humoral 63,64 ; (4) antigenicidade predita in silico utilizando-se ranqueamento combinado pela ferramentas TEPITOPE e BebiPred 63 , tendo sido selecionadas as sequências com ranqueamento de antigenicidade mais alto dentro de seu grupo funcional. Por fim, nós selecionamos 18 antígenos, dentre os quais seis já foram avaliados de forma preliminar por nosso grupo como vacinas recombinantes anti-carrapatos em bovinos 63 e/ou cães 64 , e 12 serão abordados pela primeira vez ao longo deste trabalho.…”
unclassified